Design, Molecular Modeling, MD Simulations, Essential Dynamics, ADMET, DFT, Synthesis, Anti-proliferative, and Apoptotic Evaluations of a New Anti-VEGFR-2 Nicotinamide Analogue - Eissa, Ibrahim H.; Elkaeed, Eslam B.; Elkady, Hazem; Yousef, Reda G.; Alsfouk, Bshra A.; Elzahabi, Heba S.A.; Ibrahim, Ibrahim M.; Metwaly, Ahmed M.; Husein, Dalal Z. (Current Pharmaceutical Design, 2023)
Objectives: This study aims to design and evaluate (in silico and in vitro) a new nicotinamide derivative as an inhibitor of VEGFR-2, a major mediator of angiogenesis Methods: The following in silico studies were performed; DFT calculations, molecular modelling, MD simulations, MM-GBSA, PLIP, and PCAT studies. The compound's in silico (ADMET) analysis was also conducted. Subsequently, the compound ((E)-N-(4-(1-(2-(4-(4-Chlorobenzamido)benzoyl)hydrazono)ethyl) phenyl)nicotinamide) was successfully synthesized and designated as compound X. In vitro, VEGFR-2 inhibition and cytotoxicity of compound X against HCT-116 and A549 cancer cell lines and normal Vero cell lines were conducted. Apoptosis induction and migration assay of HCT-116 cell lines after treatment with compound X were also evaluated. Results: DFT calculations assigned stability and reactivity of compound X. Molecular docking and MD simulations indicated its excellent binding against VEGFR-2. Furthermore, MM-GBSA analysis, PLIP experiments, and PCAT studies confirmed compound X’s correct binding with optimal dynamics and energy. ADMET analysis expressed its general likeness and safety. The in vitro assays demonstrated that compound X effectively inhibited VEGFR-2, with an IC50 value of 0.319 ± 0.013 μM and displayed cytotoxicity against HCT-116 and A549 cancer cell lines, with IC50 values of 57.93 and 78.82 μM, respectively. Importantly, compound X exhibited minimal toxicity towards the non-cancerous Vero cell lines, (IC50 = 164.12 μM). Additionally, compound X significantly induced apoptosis of HCT-116 cell lines and inhibited their potential to migrate and heal. Conclusion: In summary, the presented study has identified compound X as a promising candidate for the development of a novel apoptotic lead anticancer drug.
Keywords: Nicotinamide derivative